DNA barcoding of commercially important marine fish species Hipposcarus harid from the central Red Sea, Saudi Arabia - Solami Lafi Al (Oceanological and Hydrobiological Studies)
In this study, the collected fish species were identified based on morphological observations and then evaluated by DNA barcoding. The COI gene has been recognized as a biological marker for fish species identification and the objective of this study is to analyze the variable region of the COI gene in subunit I. The mitochondrial cytochrome (COI) oxidase subunit I gene was analyzed as a suitable molecular maker for the identification of three specimens of the fish species Hipposcarus harid, widely distributed in the Red Sea. The COI gene sequences in the variable region revealed variations among the fish species. The COI gene sequences in the variable region were similar to the variable region of Hipposcarus harid collected from the Northern Red Sea and all three were named: H. harid H13, H. harid H2c, and H. harid H12. The identification of the fish species collected from the Red Sea in Saudi Arabia would help ichthyologists improve the management, conservation and monitoring of economically important long-nose parrotfish species in Saudi Arabia.